Kebijakan Pengembangan Budidaya Kerang Darah (Anadara Granosa) di Kabupaten Rokan Hilir: Eksistensi Ekosistem Wilayah Pesisir Pantai - Ali Asfar; Wan Muhammad Yunus; Agus Mandar; Indra Suandy (Pelantar Press, 2025)
Blood cockles (Anadara granosa) are one of the aquatic commodities with high economic value and represent a sector with significant potential for economic development. The existence of coastal ecosystems in Rokan Hilir plays a crucial role in supporting blood cockle cultivation. These ecosystems not only provide a suitable habitat for blood cockle growth but also a sustainable base for various other economic activities. Proper management policies for these ecosystems are essential for the sustainable development of blood cockle cultivation. The aims of this research are to identify the policies related to the development of blood cockle (Anadara granosa) cultivation and to assess the existence of coastal ecosystems in Rokan Hilir, Riau. Additionally, this research aims to raise awareness among the government, private sector, and public about the importance of sustainable coastal resource and ecosystem management. It also seeks to provide insights into the economic potential of blood cockle cultivation to improve community welfare. This research used a qualitative descriptive method, involving interviews with blood cockle farmers, collectors, and local government officials. Secondary data collection and direct observations at the cultivation sites were also conducted . This research found several findings, such as: Environmental Impact, blood cockle cultivation can have both positive and negative environmental impacts. Sustainable Development Strategies, developing blood cockle cultivation requires a holistic approach and the adoption of environmentally friendly cultivation models. The application of technology in blood cockle farming is also a key strategy for sustainable development. Regulations and Policies, there is a lack of regulations regarding blood cockle cultivation and coastal management policies, including price control policies, seed collection regulations, and land allocation for farming, which sometimes lead to criminal activities. There are also no policies in place to develop effective technology for cul tivating blood cockle seeds. Based on the research findings, it is necessary to provide regular guidance, monitoring, and evaluation for blood cockle farmers. Additionally, relevant authorities should formulate appropriate regulations, develop training and extension programs, facilitate research and development of blood cockle farming technology, and promote collaboration and synergy among all sectors.